2014
DOI: 10.1073/pnas.1405635111
|View full text |Cite
|
Sign up to set email alerts
|

Tautomerism provides a molecular explanation for the mutagenic properties of the anti-HIV nucleoside 5-aza-5,6-dihydro-2′-deoxycytidine

Abstract: Significance Unlike conventional antiviral therapy, lethal mutagenesis is a therapeutic strategy that exploits the high mutation rates of certain viruses. It works by intentionally increasing the viral mutation rate, causing excessive error accumulation and viral population collapse. The mutagenic nucleoside analog 5-aza-5,6-dihydro-2′-deoxycytidine (KP1212) is specifically designed to use lethal mutagenesis against HIV. The mechanism of KP1212 mutagenesis was proposed to involve tautomerism—the repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
77
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(81 citation statements)
references
References 59 publications
4
77
0
Order By: Relevance
“…1B) and each tautomer displays distinct base-pairing preferences during replication, leading eventually to the observed mutations (8,10). This explanation is supported by our recent study, which showed a 10% G-to-A mutation exclusively at the site opposite a single KP1212 base that was introduced site-specifically into a viral vector replicating in Escherichia coli (13). We also observed multiple KP1212 tautomers at −50°C in dimethylformamide (DMF) (13); however, a detailed characterization of the tautomeric equilibrium under physiological conditions is lacking, hindering further testing of the tautomer hypothesis.…”
supporting
confidence: 60%
See 3 more Smart Citations
“…1B) and each tautomer displays distinct base-pairing preferences during replication, leading eventually to the observed mutations (8,10). This explanation is supported by our recent study, which showed a 10% G-to-A mutation exclusively at the site opposite a single KP1212 base that was introduced site-specifically into a viral vector replicating in Escherichia coli (13). We also observed multiple KP1212 tautomers at −50°C in dimethylformamide (DMF) (13); however, a detailed characterization of the tautomeric equilibrium under physiological conditions is lacking, hindering further testing of the tautomer hypothesis.…”
supporting
confidence: 60%
“…The M13 single-stranded genomes, containing one KP1212 base at a specific site, were constructed and purified as previously reported (13). The details of the primer extension reaction are described in SI Appendix and the REAP assay is described in refs.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…44 Yet, experimental evidences have indicated that tautomerism can provide a molecular explanation for the mutagenic properties. 34 Moreover, the intermolecular tautomeric equilibrium in electronic excited states 45 can favor specific tautomeric forms.…”
Section: Figurementioning
confidence: 99%